Bronquiolite obliterante pós-infecciosa: aspectos clínicos, tomográficos e funcionais.: Estudo comparativo entre crianças e adolescentes brasileiros e franceses - Natalia Silva Champs (2009)
Introduction: Post-infectious bronchiolitis obliterans (PIBO) is a chronic obstructive disease of small airways, that occurs especially after an episode of acute viral bronchiolitis (AVB) or pneumonia (PNM). There are few studies about PIBO in the southeast of Brazil and in France. Objectives: To describe and compare the major clinical, tomographic and functional characteristics of a Brazilian and French group of children and adolescents with the diagnosis of PIBO. Methods: A transversal study was carried out including 33 patients with the diagnosis of PIBO (22 male and 11 female), who were followed up during a median time of six yearsin Clinical Hospital, Belo Horizonte, Brazil, or during a median time of 4 years, at the Centre Hospitalier Universitaire Charles Nicolle, Rouen, France. Some data was collected retrospectively, but diagnosis was reviewed in 2009 by clinical and laboratorial exam. Each computed tomography was analyzed by a single radiologist, in order to identify themost common alterations. Results: Both groups presented similar demographical and clinical characteristics. The acute event possibly responsible for pulmonary lesion occurred in a median age of threeand five months for Brazilian and French children, respectively. All children presented symptoms or sighs in physical exam in the end of follow-up, which were mild from 25 to 30% of cases. Among tomographic findings, a larger proportions of Brazilians presented mosaic perfusion (p=0.004), vascular attenuation (p=0.004) and centrolobular nodules(p=0.01) compared to French patients. Pulmonary compromise was more important in Brazilian children, who presented significantly lower values of FEV1, FEF25-75% and FEV1/FVC in the first and last spirometry.Discussion: Despite ethical and geographic differences, clinical course of PIBO was severe in both counties. Nevertheless, tomographic and functional compromise was more important in Brazilian patients. This difference might be caused by variations in genetic susceptibility, virulence of infectious agent, age of diagnosis or treatment between bothcountries. Conclusions: Studies with the objective of definition of clinical criteria for HRCT in young infants and evaluation of treatment options and their criteria for indication are necessary.